2020
DOI: 10.1186/s40792-020-00896-9
|View full text |Cite
|
Sign up to set email alerts
|

Dyspnea due to an uncommon vascular tumor: leiomyosarcoma of the infrahepatic vena cava inferior

Abstract: Background Leiomyosarcoma (LMS) of the inferior vena cava (IVC) is a rare malignancy that originated from the smooth muscle tissue of the vascular wall. Diagnoses, as well as, treatment of the disease are still challenging and to date, a radical surgical resection of the tumor is the only curative approach. Case report We report on the case of a 49-year old male patient who presented with suddenly experienced dyspnea. Besides bilateral pulmonary arterial embolism, a lesion close to the head of the pancreas wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…While LMS is an exceedingly rare tumor, it is the most common primary tumor associated with the IVC [5] , typically presenting in females around fifty- to sixty-years of age [6] . There are only a few hundred reported cases of IVC LMS in the literature [4] and little is known in regard to prognosis and treatment for these tumors due to the scarcity of data; however, a study with a pooled data analysis of 377 cases revealed a very high likelihood of relapse though long-term survival is possible [9] .…”
Section: Introductionmentioning
confidence: 99%
“…While LMS is an exceedingly rare tumor, it is the most common primary tumor associated with the IVC [5] , typically presenting in females around fifty- to sixty-years of age [6] . There are only a few hundred reported cases of IVC LMS in the literature [4] and little is known in regard to prognosis and treatment for these tumors due to the scarcity of data; however, a study with a pooled data analysis of 377 cases revealed a very high likelihood of relapse though long-term survival is possible [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Tumors originating from the suprahepatic segment (segment 3) of IVC commonly have a predominantly intraluminal component and show high prevalence of intracardiac extension [ 5 , 13 , 18 ]. Gafarli S et al reported an intraluminal tumor in segment 1 with transluminal extension into the right atrium, presenting with pulmonary thromboembolism [ 21 ]. Generally, intraluminal tumors from segment 1 show distal extension in to the iliac veins [ 5 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…On Positron emission tomography (PET), these tumors show mild to intense uptake of fluorodeoxyglucose (FDG) [ 21 , 28 , 29 ]. Singh N et al [ 28 ] presented a case of intraluminal LMS showing intense FDG uptake with SUV max value of 18.…”
Section: Discussionmentioning
confidence: 99%
“…Tumors originating from the suprahepatic segment (segment 3) of IVC commonly have a predominantly intraluminal component and show high prevalence of intracardiac extension (5, 13, 18). Gafarli S et al reported an intraluminal tumor in segment 1 with transluminal extension into the right atrium, presenting with pulmonary thromboembolism (21). Generally, intraluminal tumors from segment 1…”
Section: Mixed-shows Both Intraluminal and Extraluminal Componentsmentioning
confidence: 99%
“…On Positron emission tomography (PET), these tumors show mild to intense uptake of uorodeoxyglucose (FDG) (21,28,29). Singh N et al (28) presented a case of intraluminal LMS showing intense FDG uptake with SUV max value of 18.…”
Section: Mixed-shows Both Intraluminal and Extraluminal Componentsmentioning
confidence: 99%